THE WAYS OF WORKERS IMPROVING MOTIVATION IN RAILWAY TRANSPORT - Snachov, M. P.; Pashniuk, O. O. (Science and Transport Progress, 2009)
The work is devoted to exploration of the problem of labor motivation on the railway transport of Ukraine, and the recommendations concerning the improvement of material and non-material means of strengthening the motivation in the modern society are offered.